Measuring, Managing, and Enhancing Procedural Justice in Policing: Promise and Pitfalls. (March 2018) - Worden, Robert E.; McLean, Sarah J.
The procedural justice that citizens subjectively experience with the police affects police legitimacy. The procedural justice of policing is typically not measured in police agencies, nor is it an outcome for which managers are held accountable. We examine whether and how the measurement of procedural justice would affect its management. Survey-based measures of subjective procedural justice in police contacts were reported to two departments' command staffs on a monthly basis in Compstat meetings. The impacts of thusly measuring performance were estimated. We also analyzed an indicator of procedural justice that was based on systematic observation through video and audio recording of police-citizen encounters, and we interviewed patrol officers and supervisors about supervisors' efforts to manage procedural justice. Neither indicator of police performance revealed consistent changes. However, a modest improvement on one platoon was detected. We discuss the implications for enhancing police legitimacy.